Effect of nodes position on the growth and yield of stem cutting of Sambiloto (Andrographis paniculata) - SOLIKIN SOLIKIN (Smujo International, 2018)
Solikin. 2018. Effect of nodes position on the growth and yield of stem cutting of Sambiloto (Andrographis paniculata). Nusantara Bioscience 10: 226-231. Plant propagation by cuttings can be done to produce relatively uniform quality of plant yield such as sambiloto (Andrographis paniculata (Burm.f.) ex Nees). The study aimed to determine the effect of nodes position on the growth and yield of stem cutting of sambiloto. The experiment was conducted in Purwodadi Botanic Garden in February-May 2017. The study used randomized block design with the treatment of nodes potition i.e. top, middle and base of stem cuttings. Each treatment was replicated three times. The results showed that the top stem cutting produced the highest cutting life, leaf area, leaf dry weight, root and generative organs dry weight. In contrast, the base stem cutting produced the lowest live cutting and plant growth.